A multifunctional Zr-MOF for the rapid removal of Cr2O72−, efficient gas adsorption/separation, and catalytic performance. (13th December 2019) - Zhang, Xiurong; Wang, Xia; Fan, Weidong; Wang, Yutong; Wang, Xiaokang; Zhang, Kai; Sun, Daofeng
Abstract : A three-dimensional framework with two-dimensional channels (UPC-50 ) is obtained. The stable UPC-50 is a multi-functional material for the rapid removal of Cr2 O7 2−, efficient gas adsorption/separation, and catalytic performance. Abstract : To achieve the selective adsorption of ions and light hydrocarbons by changing the pore structure, Zr-based metal–organic framework [Zr6 (μ3 -O)4 (μ3 -OH)4 (OH)4 (H2 O)4 (TB)2 ]·2DMF·2H2 O (UPC-50 ) was synthesized based on 3, 3′, 5, 5′-tetra(4-carboxyphenyl)bimesityl (H4 TB) with a steric hindrance effect under hydrothermal conditions. UPC-50 features a three-dimensional frame with two-dimensional channels and high hydrothermal and chemical stability. The Zr–OH bond in the Zr6 cluster endows UPC-50 with excellent removal capacity for trace Cr2 O7 2− in water (0.089 ppm) and efficient adsorption rate (<1 min). Moreover, through the single-component gas sorption and selectivity calculated by the IAST method, the channel of 10.6 × 16.4 Å gives UPC-50 a high adsorption capacity for C3 H6 (252.67 cm 3 g −1 ), and also shows effective separation of C3 H6 /CH4 . The unsaturated sites on the Zr6 cluster also impart excellent catalytic performance to UPC-50 in the catalytic cycloaddition reactions of CO2 with epoxides. Therefore, UPC-50 is a multi-functional material with a rapid removal capacity for Cr2 O7 2−, efficient gas adsorption/separation, and catalytic performance.